2019
DOI: 10.1111/cid.12712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical peri‐implant indices and crestal bone levels around narrow and regular diameter implants placed in diabetic and non‐diabetic patients: A 3‐year follow‐up study

Abstract: Background Studies evaluating and comparing clinical and radiographic peri‐implant indices around narrow diameter implants (NDIs; <3.3 mm) and regular diameter implants (RDIs) in type‐2 diabetes mellitus (T2DM) and non‐diabetic individuals are deficient. Objective To estimate and compare the clinical and radiographic indices around NDIs and RDIs placed in T2DM and non‐diabetic patients. Materials and Methods Eighty‐six patients requiring implant surgery in the posterior mandible were divided into two groups (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 37 publications
3
34
0
2
Order By: Relevance
“…5 Substantial research in implant dentistry has led researchers to investigate several variations in implant therapy in terms of dental biomaterials, surface modifications, and various techniques. [15][16][17] Ample research on T2DM and clinical periodontal outcomes has been peformed, 18,19 Research suggests that poor glycemic control may demonstrate poor periodontal status and that periodontal therapy may have a significant effect on the glycemic status. 9,10 Nowadays, considerable research indicates that NDIs are also indicated in areas of narrow alveolar ridges, eluding complicated surgical interventions such as bone grafts and restoring geriatric patients with minimal invasive and cost-effective treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Substantial research in implant dentistry has led researchers to investigate several variations in implant therapy in terms of dental biomaterials, surface modifications, and various techniques. [15][16][17] Ample research on T2DM and clinical periodontal outcomes has been peformed, 18,19 Research suggests that poor glycemic control may demonstrate poor periodontal status and that periodontal therapy may have a significant effect on the glycemic status. 9,10 Nowadays, considerable research indicates that NDIs are also indicated in areas of narrow alveolar ridges, eluding complicated surgical interventions such as bone grafts and restoring geriatric patients with minimal invasive and cost-effective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Numerous clinical trials investigating clinical and radiographic status of NDIs reported similar survival rates as those reported by regular diameter implants. [15][16][17] Ample research on T2DM and clinical periodontal outcomes has been peformed, 18,19 Research suggests that poor glycemic control may demonstrate poor periodontal status and that periodontal therapy may have a significant effect on the glycemic status. 20,21 From dental implant therapy standpoint, it was once believed that dental implants may not produce efficacious treatment outcomes in patients with chronic hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…20 Published data suggest that peri-implant hygiene and glycemic control are necessary for favorable postoperative evolution. 8,9,20 The immediate placement of dental implants into infected sockets remains controversial. Some studies 21 have shown no statistically significant difference in the risk of failure between dental implants placed immediately into infected sockets and dental implants placed into noninfected sites; conversely, other studies 22 have shown a three-fold increase in the risk of failure following immediate dental implant placement into an infected socket, compared with placement in an uninfected socket.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 15 articles included, 7 are clinical trials [17,[19][20][21][22]27,31], 3 are randomized controlled clinical trials [18,24,28], 3 are cohort studies [25,26,29] and 2 are a case series [23,30], all of them published between 2010 and 2018 (Table 1).…”
Section: Study Methods and Characteristicsmentioning
confidence: 99%
“…Subsequently, the abstracts were read and 45 articles were obtained. Finally, after reading the full text, 15 articles were included in the review that met the established inclusion-exclusion criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%